Patient costs and outcomes before and after the institution of a pre-eclampsia quality improvement initiative in a southwestern tertiary facility. (18th August 2019) - Banke-Thomas, Aduragbemi; Rosser, Casey; Brady, Robert; E. Shields, Laurence
Abstract: The study objective was to evaluate the effect of the California Maternal Quality Care Collaborative (CMQCC) initiative, as implemented in a southwestern U.S. tertiary hospital, on associated patient costs and outcomes. Using a quasi-experimental study design, we collected existing data (cost and patient outcomes) comparing two six-month period at the baseline and one-year follow-up. Following descriptive statistics, Chi-square tests and t -tests were used to compare categorical and continuous variables, respectively. One hundred and eighty-nine women met the inclusion criteria for the study (93 and 96 women in the baseline and follow-up period, respectively). There was no significant difference in maternal health outcomes between both periods. However, there was a significant difference for newborns with almost 90% (95%CI = 0.06–0.92; p  = .027) reduction in stillbirths in the follow-up period. There was also a significant reduction in the days between discharge and follow-up appointments ( p  < .01). Importantly, the initiative bears no additional financial burden on patients, as hospitalisation cost was unchanged. Impact statement: What is already known on this subject? In 2013, the California Maternal Quality Care Collaborative (CMQCC) set up a task force to develop guidelines for managing patients with preeclampsia based on global best practices. A previous study showed that despite system-level implementation challenges, the initiative led to significant increase in blood pressure treatments within one–hour and reduced severe maternal morbidity. What do the results of this study add? This study follows patients from admission, beyond the one–hour post-treatment and into the post-partum phase, to understand if outcomes of the initiative extend beyond the admission. While the study findings do not show any statistically significant difference in readmission before and after the initiative, nor any marked difference in maternal outcomes, it shows a significant difference in the prevalence of stillbirths at no additional cost to the patient. What are the implications of these findings for clinical practice and/or further research? Based on these findings, there is a case for scaling-up the initiative as in addition to its evidenced improvements in maternal outcomes; it is effective in improving newborn health outcomes at no additional cost. Further research, using larger sample size and exploring different care levels would be useful to verify these findings.